The effect of sappan wood extracts in treating diabetes induced in mice - Sakir, Noviana A I; Kim, Jae G (Makara Journal of Health Research, 2019)
Background: Since 2015, an estimated 415 million people had diabetes worldwide. Although, there is no scientific research related to the effectiveness of chemical substance (brazilin) in Caesalpinia sappan L. that can decrease blood glucose level in humans, many people in Sulawesi consume this wood for diabetes treatment. This study aimed to prove the effect of sappan wood extract on decreasing blood glucose levels in mice and to identify the most effective dose. Methods: Experimental research (pretest and posttest randomized controlled group design) was conducted on 20 male albino mice [body weight (bw): 20–30 g] used as alloxan-induced diabetic models and were divided into four treatment groups according to alloxan dose: control and 0.25, 0.50, and 0.75 g/kg bw (n = 5 for all groups) groups. Results: Significant effects of sappan wood extract on decreasing blood glucose levels in mice were noted in the pretest and posttest (p values are 0.754 and 0.901 respectively). Conclusions: Sappan wood extract could reduce blood glucose levels in mice with diabetes induced by alloxan at 0.25, 0.50, and 0.75 g/kg bw. The extract with 0.50 g/kg bw dose was the most effective in decreasing glucose levels in hyperglycemic mice.